China's experience with market reform for commercialization of agriculture in poor areas - Zhong, Tong; Rozelle, Scott; Stone, Bruce; Dehua, Jiang; Jiyuan, Chen; Zhikang, Xu (International Food Policy Research Institute, 1994)
This chapter is about the biggest agricultural commercialization "project" of the 1980s: China's economic reforms. It highlights the power of domestic market reform for poverty-alleviating growth, with government remaining an active force in interregional staple food markets, as well as the scope for public policy for poverty alleviation parallel with market reform. As will be shown, China's problem of absolute poverty- a cause for undernutrition in its poor areas- was significantly reduced as a result of these policies. In fact, it may be speculated that China's expansion of its poverty alleviation policy in the 1980s came partly as a result of the increased resource availability that resulted from successful commercialization and partly as a consequence of public demand for regional balance in the growth path.